Addition of Red Ginger Powder (Zingiber officinale Rosc.) in Making Herbal Tea of Avocado Leaf (Persea americana Mill.) - Dewi Fortuna Ayu; Azmi Wirzan; Faizah Hamzah (Universitas Djuanda, 2018)
The purpose of this research was to obtain the best addition of red ginger powder in making herbal tea of avocado leaf. This research used a Completely Randomized Design with five treatments and three replications. The treatments used were BJ1 (without addition of red ginger powder), BJ2 (addition of red ginger powder 2%), BJ3 (addition of red ginger powder 4%), BJ4 (addition of red ginger powder 6%), and BJ5 (addition of red ginger powder 8%). The result showed that addition of red ginger powder significantly effected water content, ash content, antioxidant activity (IC50), polyphenol content, and sensory assesment descriptively and hedonically and also overall assesment. The treatment chosen from the result was BJ5 (addition of red ginger powder 8%). This treatment had water content 4.43%, ash content 5.57%, and antioxidant activity (IC50) 44.63 µg/mL. The best treatment on descriptive test of herbal tea had tawny colour, no rotten flavour, and rather bitter and spicy. The result of hedonic test showed that colour, flavour, and taste of herbal tea were preferred by panelists and also assessment overall preferred by panelists.